2012
DOI: 10.1259/bjr/31542964
|View full text |Cite
|
Sign up to set email alerts
|

Spleen in haematological malignancies: spectrum of imaging findings

Abstract: ABSTRACT. Imaging morphology and metabolic activity of splenic lesions is of paramount importance in patients with haematological malignancies; it can alter tumour staging, treatment protocols and overall prognosis. CT, MRI and positron emission tomography (PET)/CT have been shown to be powerful tools for the noninvasive assessment of splenic involvement in various haematological malignancies. Since many haematological malignancies and non-neoplastic conditions can involve the spleen and imaging manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 25 publications
0
65
0
4
Order By: Relevance
“…Besides of the size which does not correlate with involvement, spleen is affected in one third of all lymphomas [16,17]. In this study, splenic involvement was found to be significantly higher in the lymphoma group compared to the sarcoidosis group (41.2% vs 6.5%, p = 0.001).…”
Section: Discussionmentioning
confidence: 45%
“…Besides of the size which does not correlate with involvement, spleen is affected in one third of all lymphomas [16,17]. In this study, splenic involvement was found to be significantly higher in the lymphoma group compared to the sarcoidosis group (41.2% vs 6.5%, p = 0.001).…”
Section: Discussionmentioning
confidence: 45%
“…The most common one is the homogeneous splenomegaly (without a focal lesion), which indicates diffuse infiltration of the spleen. Splenic lymphoma can also appear on the grey scale as small, focal or miliary nodules (less than 5mm), multiple large nodular lesions and bulky solid masses [1,10]. Focal lesions are most often hypoechoic relative to normal splenic parenchyma (60-70%) [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…PET/ CT tedy může nahradit histologické vyšetření měru je jednoduché a zdá se být dostačující pro měření splenomegalie. Dvourozměrné či volumometrické měření není třeba provádět [35][36][37]. Jako splenomegalie je dle revidovaných krité-rií z roku 2014 označována slezina mě-řící ve své dlouhé ose > 13 cm [18].…”
Section: Non-hodgkinův Lymfomunclassified